2019
DOI: 10.1590/2318-0331.241920180077
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis in determining water quality sampling intervals

Abstract: To make water quality series more representative, real-time monitoring techniques are developed. However, these techniques have obstacles in their use, such as high costs and difficulties in equipment installation, maintenance, and calibration. One alternative is near-real time water quality monitoring (NRTWQM), with sampling done less frequently than daily. The study objective was to evaluate, through spectral analysis, the water quality sampling frequency representativity for different catchments. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…da Silva et al (2019) in their study used spectral analysis to evaluate the representativeness of water quality sampling frequencies for different catchments. In particular, the representation of the spectral coefficients of a signal as a function of frequency results in a graph of frequency densities, which is also called Power Spectral Density (PSD).…”
Section: Spectral Analysis-power Spectral Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…da Silva et al (2019) in their study used spectral analysis to evaluate the representativeness of water quality sampling frequencies for different catchments. In particular, the representation of the spectral coefficients of a signal as a function of frequency results in a graph of frequency densities, which is also called Power Spectral Density (PSD).…”
Section: Spectral Analysis-power Spectral Densitymentioning
confidence: 99%
“…Three approaches are tested: (i) Analysing the frequency components of each parameter at each site to quantify the Nyquist frequency and supposed minimum sampling rate for determination of periodic fluctuations, proposed by Zhou (1996) and Khalil and Ouarda (2009). (ii) Using spectral analysis to determine the Power Spectral Density cumulation curve (Otis and Solomon, 1991) to determine reasonable frequencies to monitor water quality determinants; for each frequency evaluate the loss of information (da Silva et al, 2019). (iii) Analysing the limits of the spectral analysis computing spectrograms using Wavelet analysis (Torrence and Compo, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Han (2018) used a novel qualitative technique on a surface water quality monitoring system and reported 5 min as the OSF [32]. Silva et al (2019) used spectral analysis and suggested varying sampling frequencies based on the size of the watershed [33]. However, to our knowledge there is no study that has determined the OSF required for the soft sensors to train on.…”
Section: Introductionmentioning
confidence: 99%